Faktor Penghambat Mediator Non-Hakim Dalam Penyelesaian Perkara Perceraian Pada Kasus Lanjut Usia Di Pengadilan Agama Bantul - Mifta Zulfalah Azzahro Sudarmaji (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The non-judge mediator as a third party that has the rights to help the disputing parties in negotiating without any neutral case. This study aims to uncover the facts that hinder the success of non-judge mediators in carrying out mediation in elderly divorce cases at the Bantul Religious Court. This is the qualitative field research, conducted at the Religious Court Bantul from February to March conducted analytically, and by taking data based on the findings in the field with a empirical approach. The data were collected through observation, interviews, and documentation.The results of this study showed that first, Factors of elderly divorce occur because of a second marriage, the wife has menopause, old nature, economic factors, neglect of responsibilities, left by a partner because of illness. Second, the low rate of success in mediation in elderly cases at the Religious Court Bantul was caused by several factors, including: very limited time, the constancy of the parties to get divorced, the prolonged problems faced by the parties, the absence of goodwill from the parties not attending the mediation process.